Cationic gemini surfactant stimulates amyloid fibril formation in bovine liver catalase at physiological pH. A biophysical study. Issue 71 (8th December 2020) - Khan, Javed Masood; Malik, Ajamaluddin; Rehman, Md. Tabish; AlAjmi, Mohamed F.; Ahmed, Mohammad Z.; Almutairi, Ghada Obaid; Anwer, Md. Khalid; Khan, Rizwan Hasan
Abstract : Surfactant molecules stimulate amyloid fibrillation and conformational switching in proteins but the mechanisms by which they accomplish these effects are unclear. Abstract : Surfactant molecules stimulate amyloid fibrillation and conformational switching in proteins but the mechanisms by which they accomplish these effects are unclear. A cationic gemini surfactant, C16 C4 C16 Br2, with two positively charged heads and two-16C hydrophobic tails induces the amyloid fibrillation of bovine liver catalase (BLC) in vitro at physiological pH. The BLC transformed into amyloid aggregates in the presence of low concentrations (2–150 μM) of C16 C4 C16 Br2 at pH 7.4, as confirmed by the use of several biophysical techniques (Rayleigh light scattering (RLS), intrinsic fluorescence, thioflavin T fluorescence (ThT), far-UV circular dichroism, and transmission electron microscopy). The secondary structure of BLC also changed according to the concentration of C16 C4 C16 Br2 : the α-helical structure of BLC decreased in the presence of 2–100 μM of C16 C4 C16 Br2 but at concentrations above 200 μM BLC regained a α-helical structure very similar to the native BLC. In silico molecular docking between BLC and C16 C4 C16 Br2 suggest that the positively charged heads of the surfactant interact with Asp127 through attractive electrostatic interactions. Moreover, a Pi-cation electrostatic interaction and hydrophobic interactions also take place between the tails of the surfactant and BLC. The stability of the BLC–C16 C4 C16 Br2 complex was confirmed by performing a molecular dynamics simulation and evaluating parameters such as root mean square deviation (RMSD), root mean square fluctuation (RMSF), radius of gyration ( R g ), and solvent accessible surface area (SASA). Apart from its aggregation inducing properties, the gemini surfactant itself causes toxicity to the cancerous cell (A549): which is confirmed by MTT assay. This work delivers new insight into the effect of cationic gemini surfactants in amyloid aggregation and paves the way to the rational design of new anti-amyloidogenic agents.